PENGEMBANGAN MODEL MODUL IPA BERBASIS PROBLEM SOLVING METHOD BERDASARKAN KARAKTERISTIK SISWA DALAM PEMBELAJARAN DI SMP/MTs - Wenno, Izaak H (LPMPP Universitas Negeri Yogyakarta, 2010)
Abstract: Developing Science Module Models Based on the Problem SolvingMethod on the Basis of Students Learning Characteristics in SMP/MTs. Thisstudy aims to investigate the learning process in the laboratory using modulesbased on the problem solving method, effects of the module models on thestudents achievement, the effectiveness of the modules, and the evaluation systemin the modules. This study was a research and development study employing amodel by Borg and Gall. The research subjects comprised students, teachers, andprincipals. The data were collected through observations and interviews andanalyzed using the descriptive technique. The results show that the module models,namely experiment and non-experiment student work sheets based on the problemsolving method, and the evaluation system in science learning can be used as analternative.Keywords : science module models, problem solving method, and science teaching